"Relaxed" natural kinds and psychiatric classification. (December 2018) - Varga, Somogy
Abstract: This paper starts out highlighting a particular criticism that psychiatry faces and continues by investigating approaches to classification in psychiatry that operate with a "relaxed" (non-essentialist) notion of natural kind. Two accounts are examined, one by Rachel Cooper (2005; 2013) and one based on the work of Richard Boyd (1991; 1999; 2003; 2010). While these accounts do not directly pursue such a goal, the main aim is to probe whether deploying a "relaxed" notion of natural kind would be able to neutralize the criticism. While the conclusion is in the negative, the analysis raises doubts that it is possible to completely neutralize this criticism without assuming an overly simplistic view of the causal structure of the world. Highlights: Critics claim that psychiatry deploys a conventionalist classification based on non-epistemic evaluative judgments. Classification in psychiatry can operate with a "relaxed" (non-essentialist) notion of natural kind. A "relaxed" notion of natural kind is too permissive to completely neutralize this criticism.